Pengaruh Terapi Butterfly Hug Terhadap Tingkat Kecemasan Akademik Pada Remaja Putri di Pondok Pesantren Jenu Tuban - Septyandini, Phinasty; Nur Faizah, Hanim; Putri Ryandini, Tiara; Suhartono, Suhartono (Pustaka Galeri Mandiri, 2025)
Academic anxiety is defined as excessive feelings of fear and worry in academic situations. Academic anxiety is an emotional reaction or negative state that can disrupt the learning process and affect academic performance. One non-pharmacological intervention that can be used to reduce academic anxiety is butterfly hug therapy. This study aims to determine the effect of butterfly hug therapy on the level of academic anxiety among adolescents females at Islamic Boarding School Jenu Tuban. The research design employed in this study is a quantitative pre-experimental using a one-group pre-post test design approach with a cohort approach. The population in this study consists of 70 adolescents females at Islamic Boarding School Jenu Tuban. The sampling technique used is non-probability sampling with purposive sampling, resulting in 67 respondents. The instruments used in this study are the academic anxiety questionnaire and the Standard Operating Procedure (SOP) for butterfly hug therapy. The research results obtained after conducting the Wilcoxon test with a significance level of a ? 0.05 with a p value = 0.000 < 0.05 which means H1 is accepted, namely there is an effect of butterfly hug therapy on the level of academic anxiety in adolescents. Butterfly hug therapy is an effective non-pharmacological intervention proven to reduce academic anxiety levels, which in turn can enhance focus in learning and improve academic performance. From the description above, it can be concluded that butterfly hug therapy has an effect on the level of academic anxiety in female adolescents at the Jenu Tuban Islamic Boarding School